Heterogeneity and homeostasis in the validity of the muliza Falsía. Different narratives of the song - Asto Carbajal, Tatiana Valeria (2022)
During our Peruvian Republic, various composers have enriched the popular musical imaginary by immortalizing songs that have echoed from the past to our present. One of these pieces in question is the unforgettable muliza Falsía by Emilio Alanya Carhuamaca and Pablo Pastor Díaz Reynoso. With the aim of studying the song from the literary discipline, this research follows the line of interdisciplinary studies between literature and music. The main problem that will guide this article will be: What characteristic elements of literary studies intervene within the validity of the muliza Falsía? These elements will be two: the psychodynamic homeostasis of oral tradition literature and the discursive heterogeneity. We will see how these elements explain the updating of new interventions in the lyrics of the song making possible different reinterpretations of the muliza, that is, we will evidence its different narratives. On the one hand, homeostasis will manifest itself through a series of changes and modifications in the lyrics and musical codes that intervene in the song over the years in accordance with the social context. On the other hand, heterogeneity will make visible the presence of three social subjects.